9th International Conference on Cognitive Science, 27-19 August 2013 - Universiti Malaysia Sarawak, Faculty of Cognitive Sciences & Human Development (Universiti Malaysia Sarawak, 2013)
9th International Conference on Cognitive Science (ICCS 2013) Hilton Kuching, Sarawak. 27-19 August 2013. ICCS 2013 Launching and Opening Ceremony